1987
DOI: 10.1007/bf00284472
|View full text |Cite
|
Sign up to set email alerts
|

Gene-rich chromosome regions and autosomal trisomy

Abstract: Cases of autosomal trisomy and trisomy mosaicism among liveborn infants are reviewed, and a second case of chromosome 3 trisomy mosaicism is described. The occurrence of autosomal trisomy for a particular chromosome is in general negatively correlated with the number of genes which have been localized to that chromosome. It is also positively related to the Q-brightness of the chromosome, which reflects its content of intercalary heterochromatin. Furthermore there are significantly fewer autosomal trisomics fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…One adult was reported to have severe mental retardation, short stature, and dysmorphic facies (Kuhn et al, 1987). One adult had short stature, coloboma, hip dislocation, and Bartter syndrome (DeKeyser et al, 1988).…”
Section: /47+3mentioning
confidence: 99%
“…One adult was reported to have severe mental retardation, short stature, and dysmorphic facies (Kuhn et al, 1987). One adult had short stature, coloboma, hip dislocation, and Bartter syndrome (DeKeyser et al, 1988).…”
Section: /47+3mentioning
confidence: 99%
“…These chromosomes have varying influences as trisomies during development. Trisomy 1 is associated with very early fetal death [Kuhn et al, 1987]; the paternal contribution to trisomy 1 is not known. Trisomy 16 is the most common form of trisomy found among spontaneously aborted fetuses [21.5%;Eiben et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Watt et al (1987) demonstrated trisomy 1 in an eight-cell embryo. These findings have led to the assumption that trisomy 1 does occur, but is lethal very early in fetal development, and that there has been no paternal contribution for trisomy 1 known until now (Kuhn et al, 1987). Trisomy 16 also is typically of maternal origin, and only a few paternally derived cases have been reported (Hassold et al, , 1996.…”
Section: Epidemiological Studiesmentioning
confidence: 99%